2014
DOI: 10.3389/fncel.2014.00177
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 4 (ATF4) modulates post-synaptic development and dendritic spine morphology

Abstract: The ubiquitously expressed activating transcription factor 4 (ATF4) has been variably reported to either promote or inhibit neuronal plasticity and memory. However, the potential cellular bases for these and other actions of ATF4 in brain are not well-defined. In this report, we focus on ATF4's role in post-synaptic synapse development and dendritic spine morphology. shRNA-mediated silencing of ATF4 significantly reduces the densities of PSD-95 and GluR1 puncta (presumed markers of excitatory synapses) in long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(95 citation statements)
references
References 48 publications
(52 reference statements)
11
84
0
Order By: Relevance
“…The infection efficiency was ~90%. We also observed that an shRNA targeted to another sequence of rat ATF4 had no effect on ATF4 expression (Figure 1A) and used this as a control (shCTRL2) along with another control (shCTRL1) in which 5 bases of shATF4 were changed (Liu et al, 2014). To verify infection efficiency and spreading of the lentiviral particles in vivo , we injected adult mouse hippocampi with an empty lenti-GFP vector, sacrificed them 1 month later and assessed GFP expression.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The infection efficiency was ~90%. We also observed that an shRNA targeted to another sequence of rat ATF4 had no effect on ATF4 expression (Figure 1A) and used this as a control (shCTRL2) along with another control (shCTRL1) in which 5 bases of shATF4 were changed (Liu et al, 2014). To verify infection efficiency and spreading of the lentiviral particles in vivo , we injected adult mouse hippocampi with an empty lenti-GFP vector, sacrificed them 1 month later and assessed GFP expression.…”
Section: Resultsmentioning
confidence: 93%
“…Both the amplitude and frequency of mEPSCs were significantly reduced (20% and 40%, respectively) in ATF4 down-regulated cultured hippocampal neurons compared to controls (Figures 4A,B,C). To confirm that these results were not due to off-target effects, we performed a rescue experiment in which the neurons were co-infected with lentiviruses expressing shATF4 and an ATF4 transcript (ATF4add) conservatively mutated to render it unresponsive to shATF4 (Liu et al, 2014). This results in knockdown of endogenous and over-expression of exogenous ATF4 (Figure 4D).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations